2015
DOI: 10.1007/s11695-015-1650-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Prophylactic Cholecystectomy in Patients Undergoing Bariatric Bypass Surgery

Abstract: Nearly 50 % of our patients had either experienced gallstones before LRYGB or developed gallstones after LRYGB. In the group with new gallstone development, 50 % required emergency cholecystectomy. These results, together with the reported better quality of life after a combined procedure and the reported economic benefits, support the use of concomitant prophylactic cholecystectomy in patients undergoing LRYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 33 publications
0
23
0
4
Order By: Relevance
“…Because there is no clear consensus about the best management, various options have been proposed over the last decades [11,12]. Several studies have assessed the advantages and disadvantages of concomitant gallbladder removal during the bariatric procedure [13][14][15][16][17][18][19][20]. Among the advantages observed are that morbidity is not increased, the procedure is safer and cheaper with just an extra 30 min of operation time and no additional hospital stay, a minimal complication rate, and an improved quality of life [3,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there is no clear consensus about the best management, various options have been proposed over the last decades [11,12]. Several studies have assessed the advantages and disadvantages of concomitant gallbladder removal during the bariatric procedure [13][14][15][16][17][18][19][20]. Among the advantages observed are that morbidity is not increased, the procedure is safer and cheaper with just an extra 30 min of operation time and no additional hospital stay, a minimal complication rate, and an improved quality of life [3,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the advantages and disadvantages of concomitant gallbladder removal during the bariatric procedure [13][14][15][16][17][18][19][20]. Among the advantages observed are that morbidity is not increased, the procedure is safer and cheaper with just an extra 30 min of operation time and no additional hospital stay, a minimal complication rate, and an improved quality of life [3,[13][14][15][16][17][18]. In contrast, a meta-analysis that included 13 studies (>6000 patients) indicated that concomitant cholecystectomy should be generally avoided; rather, it should be performed only in patients with symptomatic gallbladder disease, as bariatric surgery alone had lower complication and mortality rates (0.1 vs. 0.2 %, p = 0.012) than concomitant surgery [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, elective cholecystectomy at the time of bariatric surgery is recommended by some centres, but it can be technically challenging, with a higher incidence of complications 6–9. There are many conflicting retrospective case series on this particular topic, with some suggesting that the high rates of gall bladder disease and subsequent need for emergency procedures necessitate performing concomitant gall bladder surgery at index gastric bypass 10 11. However, there is no expert or international consensus on cholecystectomy for this indication.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, We read with interest the article of Amstutz et al [1] and congratulate the authors for selecting such as a practical and important subject. Basically, gallbladder/gallstone problem is associated with successful weight loss following bariatric surgery.…”
mentioning
confidence: 99%